A Novel Capacitive Method for Urodynamic Measurements That is Suitable for Home Use: Nova metoda merjenja urodinamike, primerna za domačo uporabo na osnovi kapacitivnosti - Nikolić, Gregor; But, Igor; Stožer, Andraž; Kramberger, Iztok (Acta Medico-Biotechnica, 2021)
Purpose: Urinary incontinence is highly prevalent in both women and men. Urodynamic testing is essential for diagnosis, but a gap exists in the usefulness of simple assessments that do not provide sufficient data, and devices that provide the necessary data, but are used primarily in clinics and clinical trials. This study considered the existing methods of urodynamics testing and developed a device that was both effective and suitable for home use.Methods: A review of existing urodynamic methods led to development of a capacitive device. We created a device with sensor electrodes placed on the outside of a specimen container. The functionality of the electrodes and performance of the novel capacitive device were compared with that of a gravimetric device (Dorado KT, Laborie Medical Technologies, Mississauga, ON, Canada) used at the University Clinical Center, Maribor.Results: Measurements of fluid volume (p = 0.936), maximum (p = 0.327), and mean (p = 0.136) flow observed with the two devices were not significantly different. Graphical analysis of collected volumes and flow variation over time show a high degree of overlap.Conclusion: Compared with previously developed urodynamics testing devices, the capacitance method and the performance of this device represent an advance. The precision of the measurements needs improvement and did not fully address the recommendations of the International Continence Society, but he use of additional sensor electrodes is expected to improve performance. Extending the functionality as a standalone capacitive device for home use and upgrading with wireless access by mobile systems would allow for additional benefits beyond current voiding diaries.
Keywords: urodinamske meritve; urodinamika; neinvazivne meritve urodinamike; simptomi spodnjih sečil; disfunkcija uriniranja; prekomerno dejaven mehur